Pengaruh Kebiasaan Belajar dan Lingkungan Keluarga terhadap Hasil Belajar Peserta Didik Kelas VIII di SMP Negeri 2 Sawan - I Made Aditya Krisnananda; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the partial and simultaneous effects of study habits and family environment on the learning outcomes in Social Studies (IPS) of eighth-grade students at SMP Negeri 2 Sawan. This research employed a quantitative approach with a causal design. The population consisted of students from classes VIII A, VIII B, and VIII E whose average scores were below the Minimum Competency Criteria (KKM), totaling 84 students. The sampling technique used was saturated sampling. Data were collected through questionnaires, documentation, and observation, and analyzed using multiple linear regression. The results of the study indicate that: (1) study habits have a significant effect on students’ learning outcomes, with a significance value of 0.000 < 0.05; (2) the family environment has a significant effect on students’ learning outcomes, with a significance value of 0.003 < 0.05; and (3) study habits and family environment simultaneously have a significant effect on students’ learning outcomes, with a significance value of 0.000 < 0.05. Based on these findings, it can be concluded that study habits and the family environment are important factors in improving students’ academic performance.( study habits; family environment; learning outcomes).